2018
DOI: 10.1111/jtxs.12362
|View full text |Cite
|
Sign up to set email alerts
|

How are macronutrient intake, BMI, ethnicity, age, and gender related to the composition of unstimulated saliva? A case study

Abstract: Saliva plays an important role in food oral processing. From the breakdown of food structures to the binding of flavor compounds and the formation of a swallowable bolus, saliva is essential for the perception and appreciation of foods. Identifying the factors that affect saliva composition is, therefore, necessary to understand the differences in eating behavior, food perception, and preference across different consumer groups. This article aims to highlight the importance of considering saliva variability wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
(75 reference statements)
6
23
2
1
Order By: Relevance
“…Caucasian and Chinese, Asian participants ( Table 7.2). Similar results were obtained also by Mosca et al (2019) and Pedrotti et al (2019) as no differences in saliva flow rate were observed between groups with the same ethnicity and nationality (i.e. Dutch, Caucasian and Chinese, Asian).…”
Section: Participant Characteristicssupporting
confidence: 83%
See 2 more Smart Citations
“…Caucasian and Chinese, Asian participants ( Table 7.2). Similar results were obtained also by Mosca et al (2019) and Pedrotti et al (2019) as no differences in saliva flow rate were observed between groups with the same ethnicity and nationality (i.e. Dutch, Caucasian and Chinese, Asian).…”
Section: Participant Characteristicssupporting
confidence: 83%
“…Considering that the two groups tested were homogeneous in their age and sex, this study focused on potential differences related to nationality and ethnicity. To the best of our knowledge, minimal research has been conducted to date addressing possible differences in oral physiology between participants of different ethnicities Mosca et al, 2019;Pedrotti et al, 2019;Xue & Hao, 2006). Similarly, a few studies have investigated whether possible cross-cultural differences influence food texture perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers present in saliva can be used to differentiate individuals (Lucas, Barbosa, Castelo, & Gavião, ). The quantification of salivary differences/similarities between different consumer groups can provide useful information for the design of products targeting specific markets (Mosca et al, ).…”
mentioning
confidence: 99%
“…Kadınlardaki tükürük akış oranının erkeklere göre %32 daha az olduğu gösterilmiştir. 17 Tükürük akışında azalma ağız sağlığını etkileyen bir durumdur ve tükürük akış miktarının azalması ile ortaya çıkan ağız kuruluğu en sık görülen oral hastalık olan diş çürüğü ile ilişkilidir. 16 Ayrıca, sporcularda egzersiz sırasında da tükürük akış hızının azaldığı, pH değerinin düştüğü ve ağız kuruluğunun arttığı ve bu durumun da çürük oluşumu için yüksek risk oluşturduğu tespit edilmiştir.…”
unclassified